Applying the distance-to-target weighting methodology to assess the environmental performance of palm oil mills in Nigeria - Mohammed Engha Isah; Zhengyang Zhang; Kazuyo Matsubae (Environmental Research: Infrastructure and Sustainability)
Life cycle assessment (LCA) studies must present results in a clear and comparable manner to support decision-making, particularly for policymakers who often prioritize greenhouse gas (GHG) emissions while neglecting other environmental impacts. Decision making in favor of or against a product or it is alternatives therefore often requires weighing of environmental impacts. This study develops a life cycle impact assessment (LCIA) weighting method to evaluate the environmental performance of small, semi-mechanized, and large-scale palm oil mills in Nigeria using a gate-to-gate approach. The distance-to-target ecological scarcity weighting methodology was applied across four environmental impact categories (GHG, freshwater resources, emissions to air and primary energy resources). Results indicate that semi-mechanized mills exhibit the highest overall environmental burden than smallholder and large-scale mills and accounted for 61% of the total overall single score primarily due to GHG emissions from fossil fuel combustion. Across all mill types, GHG emissions emerge as the dominant contributor to environmental degradation, underscoring the need for renewable energy integration. Sensitivity analysis highlights that policies targeting GHG emissions and freshwater use significantly influence environmental performance. By employing a country-specific, policy-derived LCIA approach, this study effectively illustrates trade-offs between mill types, making the findings accessible to both LCA experts and non-experts. The results emphasize the importance of technological and policy interventions to promote cleaner and more sustainable palm oil production. Considering the controversy and uncertainties associated with weighting, we recommend using weighting as a supplementary tool in line with ISO 14 040 and 14 044.